Associations between temporary employment and occupational injury: what are the mechanisms?. Issue 6 (23rd February 2006) - Benavides, F G; Benach, J; Muntaner, C; Delclos, G L; Catot, N; Amable, M
Abstract : Objective: To determine whether observed higher risks of occupational injury among temporary workers are due to exposure to hazardous working conditions and/or to lack of job experience level. Methods: Data systematically recorded for 2000 and 2001 by the Spanish Ministry of Labour and Social Affairs on fatal and non-fatal traumatic occupational injuries were examined by type of employment and type of accident, while adjusting for gender, age, occupation, and length of employment in the company. In the study period there were 1500 fatal and 1 806 532 non-fatal traumatic occupational injuries that occurred at the workplace. Incidence rates and rate ratios (RR) were estimated using Poisson regression models. Results: Temporary workers showed a rate ratio of 2.94 for non-fatal occupational injuries (95% CI 2.40 to 3.61) and 2.54 for fatal occupational injuries (95% CI 1.88 to 3.42). When these associations were adjusted by gender, age, occupation, and especially length of employment, they loose statistic significance: 1.05 (95% CI 0.97 to 1.12) for non-fatal and 1.07 (95% CI 0.91 to 1.26) for fatal. Conclusions: Lower job experience and knowledge of workplace hazards, measured by length of employment, is a possible mechanism to explain the consistent association between temporary workers and occupational injury. The role of working conditions associated with temporary jobs should be assessed more specifically.